Green synthesis of Piper nigrum copper-based nanoparticles: in silico study and ADMET analysis to assess their antioxidant, antibacterial, and cytotoxic effects - Kiranmayee, Modumudi; Rajesh, Nambi; Vidya Vani, M.; Khadri, Habeeb; Mohammed, Arifullah; Chinni, Suresh V.; Ramachawolran, Gobinath; Riazunnisa, Khateef; Moussa, Ashaimaa Y. (Frontiers in Chemistry, 2023)
Nanobiotechnology is a popular branch of science that is gaining interest among scientists and researchers as it allows for the green manufacturing of nanoparticles by employing plants as reducing agents. This method is safe, cheap, reproducible, and eco-friendly. In this study, the therapeutic property of Piper nigrum fruit was mixed with the antibacterial activity of metallic copper to produce copper nanoparticles. The synthesis of copper nanoparticles was indicated by a color change from brown to blue. Physical characterization of Piper nigrum copper nanoparticles (PN-CuNPs) was performed using UV-vis spectroscopy, FT-IR, SEM, EDX, XRD, and Zeta analyzer. PN-CuNPs exhibited potential antioxidant, antibacterial, and cytotoxic activities. PN-CuNPs have shown concentration-dependent, enhanced free radical scavenging activity, reaching maximum values of 92%, 90%, and 86% with DPPH, H2O2, and PMA tests, respectively. The antibacterial zone of inhibition of PN-CuNPs was the highest against Staphylococcus aureus (23 mm) and the lowest against Escherichia coli (10 mm). PN-CuNPs showed 80% in vitro cytotoxicity against MCF-7 breast cancer cell lines. Furthermore, more than 50 components of Piper nigrum extract were selected and subjected to in silico molecular docking using the C-Docker protocol in the binding pockets of glutathione reductase, E. coli DNA gyrase topoisomerase II, and epidermal growth factor receptor (EGFR) tyrosine to discover their druggability. Pipercyclobutanamide A (26), pipernigramide F (32), and pipernigramide G (33) scored the highest Gibbs free energy at 50.489, 51.9306, and 58.615 kcal/mol, respectively. The ADMET/TOPKAT analysis confirmed the favorable pharmacokinetics, pharmacodynamics, and toxicity profiles of the three promising compounds. The present in silico analysis helps us to understand the possible mechanisms behind the antioxidant, antibacterial, and cytotoxic activities of CuNPs and recommends them as implicit inhibitors of selected proteins.